2017
DOI: 10.1167/iovs.17-21948
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Course During the Femtosecond Laser-Assisted Cataract Surgery in Porcine Cadaver Eyes

Abstract: PURPOSE. Femtosecond laser-assisted cataract surgery (FLACS) is an increasingly common procedure. Most laser systems require corneal applanation and thereby increase intraocular pressure (IOP). The purpose of the present study was to evaluate the IOP changes that occur during the FLACS procedure performed using the Catalys femtosecond laser system. METHODS. IOP was measured by direct cannulation of the vitreous body of porcine cadaver eyes (N ¼ 20). By inserting a second cannula connected to a water column, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
(35 reference statements)
0
16
2
3
Order By: Relevance
“…; Sperl et al. ). However, comparison of the results of those two studies indicates a correlation between the baseline IOP and the IOP during vacuum application.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…; Sperl et al. ). However, comparison of the results of those two studies indicates a correlation between the baseline IOP and the IOP during vacuum application.…”
Section: Discussionmentioning
confidence: 96%
“…; Sperl et al. ). In contrast, studies investigating the Ziemer LDV Z8 platform showed about 10 mmHg higher IOP values with comparable preoperative baseline IOP (Williams et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Besides, the rapid development of femtosecond (10 − 15 s) lasers over the past two decades has opened up new applications in ophthalmic surgery [12] such as FLEx (FS laser lenticular extraction), SMILE (small-incision lenticular extraction), FLACS (FS laserassisted cataract surgery), etc. Many studies have revealed significant IOP increases during FS laser-assisted procedures [15][16][17]. In spite of changes in intraocular pressure, a phenomenon called retinal autoregulation [18][19][20][21] is able to maintain blood flow and oxygen supply to the fundus at a constant level.…”
Section: Discussionmentioning
confidence: 99%
“…Swine are increasingly being used in ophthalmology and vision science research to model various ocular diseases (Stricker-Krongrad et al, 2016), develop surgical techniques (Tasaka et al, 2013; Ibarz et al, 2016; McQuaid et al, 2016; Nanavaty and Kubrak-Kisza, 2017; Speri et al, 2017; Tandogan et al, 2016), novel therapies and intervention strategies (Umazume et al ., 2013; Scott et al, 2015; Wang et al, 2016; Lin et al, 2017; Drozhz- hyna et al, 2017; Cong et al, 2018) to prevent vision loss in humans due to similar ocular anatomy and physiology (Beauchemin, 1974; De Schaepdrijver et al, 1992; Gerke et al, 1995; Bartholomew et al, 1997; Ninomiya and Inomata, 2006; Acosta et al ., 2009; Sanchez et al ., 2011). Although studies (Bartholomew et al, 1997; Faber et al, 2008; Jay et al, 2008) have examined anatomical features of the domestic swine cornea, none have compiled a characterization of miniature corneal morphology at both the light and electron microscopic level.…”
mentioning
confidence: 99%